Midwifery Communication Relations in The Team Midwifery with Complete Medical Record Documents - Sofia Merylista (Universitas Nurul Jadid Paiton Probolinggo, East Java, Indonesia, 67291, 2025)
Midwifery communication in the Midwifery team is important for a person and for nurses and the health team so good communication must be implemented by all social beings so that communication is important for all social beings. Midwifery Care medical records are files containing Midwifery records and documents regarding patient identity, examination, treatment, procedures and other services that have been provided to patients. This research identifies communication within the Midwifery team and the completeness of medical record documents for nursing care, to determine the relationship between Midwifery communication within the Midwifery team and the completeness of medical record documents for Midwifery care at Elizabeth Lela Hospital. This research is quantitative research with a correlation method. The total sample is 9 respondents. The sampling technique used is purposive sampling. Data collection using observation. Data were analyzed using the Spearman Rank test. Analysis results using Spearman Rank shows that the independent and dependent variables obtained sig results. P-value = 0.000 and r = 0.968. Midwifery communication in the Midwifery team is in the inadequate category, Completeness of medical record documents for Midwifery Care is in the incomplete category, there is a relationship between Midwifery communication in the Midwifery team and completeness of medical record documents for Midwifery care at Elizabeth Lela Hospital.